Impact of indoor environmental quality on cognitive function : an analysis of thermal comfort and carbon dioxide levels in New Zealand primary schools : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Construction at Massey University, Auckland, New Zealand - Tookey, Lara (Massey University, 2024)
This study investigates the relationship between indoor environmental quality (IEQ) parameters—specifically thermal comfort and carbon dioxide (CO₂) levels—and the cognitive functioning of primary school students in New Zealand. The research employs a multi-faceted approach, combining field measurements, surveys, and cognitive assessments across multiple geographical regions and seasons. Utilising the SKOMOBO Indoor Environmental Monitoring (IEM) platform and magnetic sensors, the study provides detailed analyses of classroom conditions before and after the COVID-19 pandemic, revealing significant seasonal variations in temperature and ventilation effectiveness. The research explores factors influencing window-opening behaviours and their impact on IEQ and thermal comfort through questionnaires, observational studies, and sensor data. Additionally, it examines the effects of different environmental conditions on students’ concentration, reasoning, and memory, using controlled experiments and the Creyos online cognitive testing platform. Key findings indicate that optimal thermal comfort and good ventilation significantly enhance cognitive abilities, while elevated CO₂ levels and temperature fluctuations negatively impact performance. The study emphasises the critical role of proper heating, cooling, and ventilation strategies in maintaining a healthy and conducive learning environment. Based on these insights, the research proposes evidence-based recommendations for improving IEQ in primary schools, including optimising natural ventilation, enhancing insulation and heating systems, and implementing continuous monitoring of classroom conditions. The study highlights the importance of stakeholder involvement in driving systemic changes to create healthier, more effective learning spaces that support students’ cognitive development and academic success.
Keywords: indoor air quality, indoor environmental quality, thermal comfort, ventilation, carbon dioxide, indoor temperature, airing, window opening behaviour, natural ventilation, indoor environmental monitoring, cognition, primary schools, New Zealand; 339999 Other built environment and design not elsewhere classified; 410402 Environmental assessment and monitoring